Logistics During Population and Animals Evacuation in Case of Extraordinary Incidents and Crisis Events - Paweska, Marcin; Ristvej, Jozef (Communications - Scientific letters of the University of Zilina, 2018)
Evacuation is one of the main tasks of administration and its forces and resources in different types of extraordinary events, as well as natural and anthropogenic (non-military and military events) unusual/emergency situations. Evacuation at the level of normative acts and plans is precisely defined and categorized. Existing normative documents and regulations are described in detail and govern to carry out the evacuation of population. This is not the case for animal and property evacuation, which is often treated in general terms and considered to be organized in similar manner to evacuation of people. In the evacuation process of animals, the specific of this process must be taken into account, because badly prepared and performed evacuation may bring more harm than benefit. Hence, the aim of this article is to present, selected essential and specific issues relating to the evacuation of animals, based on theory provisions of the normative and practical experience of the authors.